POLA PEWARISAN SIFAT DAYA HASIL KACANG TANAH HASIL PERSILANGAN cv. KELINCI DAN US 605 DALAM KONDISI TERCEKAM KEKERINGAN - Adisyahputra; Sudarsono; K. Setiawan (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
The aim of this research was to examine the yield characters of peanut in drought stress. The experiment was conducted by using of peanut cv. Kelinci that is sensitive genotype as female parent and US 605 which is tolerant genotype as male parent, including the F2 population F1 offspring from hybrid cv. Kelinci (P1) with US 605 (P2). The number of pods, amount of filled pods, dry weight of pods, dry weight of seed, the number of seeds, are measured during harvest. Expression of all yield characters were influenced by genetic factor, except the variable weight of seed. All of yield show the quantitative and qualitative characters. The result analysis of Mendelians genetic yield showed all characters were controlled by 2 until 3 gene with the dominant and resesif epistasis combination pattern. Result from joint scalling test analysis showed all variable were not only determined by additive and dominant influence but also by genetic interaction. Additive influence with the high narrow sense heritability most of all variables together can give opportunity to obtain tolerant peanut line with heigh yield.